Perbandingan Biaya dan Waktu Pembangunan Jembatan Menggunakan Box Culvert dengan Balok Girder di Karangan Kidul Kabupaten Gresik - Rio Rahma Dhana; Rasio Hepiyanto; Nico Firmansyah (Universitas Batanghari Jambi, 2026)
A Bridges are vital infrastructures that connect transportation routes separated by rivers or other physical barriers. This study analyzes the comparison of cost and time efficiency in the construction of the Karangan Kidul Bridge, Gresik Regency, using two structural alternatives: box culvert and girder beam. The research applied the Program Evaluation and Review Technique (PERT) to estimate project duration and the Crashing Project method to accelerate schedules by considering additional overtime costs. Data were collected through field surveys, contractor interviews, and project documents such as the bill of quantities and time schedule. The analysis shows that the normal duration of construction using a box culvert is 119 days, while using a girder beam is 118 days. With the crashing approach, the box culvert can be accelerated to 106 days (1-hour overtime), 95 days (2-hour overtime), and 82 days (3-hour overtime), with additional costs ranging from IDR 709,091,569.18 to IDR 755,596,130.01. Meanwhile, the girder beam option can be accelerated to 104 days, 94 days, and 89 days, with additional costs between IDR 1,109,586,454.03 and IDR 1,158,716,492.98. The cost difference between both alternatives exceeds IDR 400 million, while the time difference is only 1 day. Therefore, the box culvert is considered more economical for this project, even though the girder beam provides relatively comparable flexibility in schedule acceleration.